Implementação de recursos Interativos através do protocolo Open Sound Control: um experimento com arte digital no SESI Museu Digital de Campina Grande - Santos Júnior, Reinaldo Toscano dos (2021)
This research deals with the field of digital art in a museological context that involves the relationship between art, science and technology. We carried out a historical overview, from the 1960s, a period in which the first works of digital art using computational resources began to appear, up to the present day. To contextualize concepts and definitions that surround the digital art landscape. We relate knowledge from the fields of art and technology to deal with the process of artistic creation with this bias, understanding the importance of using algorithms in digital arts. We conducted a survey of data on the state of the art on digital arts in museums, based on a literature review, listing works that involved digital art in museums, between the years 2016 and 2019 in the digital databases of for Computing Machinery (ACM) and the Institute of Electrical and Electronics Engineers (IEEE); We relate digital art works using emerging technologies in order to verify the limits of current artistic production in this segment. We complement the foundation of our research with a survey of digital / interactive museums, in Brazil and worldwide, observing their main characteristics and relationships with their visitors. Based on a preliminary study, we verified that the Open Sound Control (OSC) protocol can be a versatile, flexible, precise and interoperable alternative in the implementation of interactivity in multimedia systems, the verification of its applicability in the context of digital arts was one of the objectives of this research. We carried out an experimental phase to propose the implementation of interactive resources in the Panoramic Projection Room of SESI Digital Museum in Campina Grande, taking advantage of the pre-installed infrastructure in the museum, adding hardware and software resources to make the implementation feasible. We proposed a prototype of the implementation of interactive streaming in the projection room, based on the development of a Proof of Concept. Finally, we present a discussion that related the exploratory and experimental phases of our research to create reflections on the development of the proposed implementation in the current and future context of digital arts.